2022
DOI: 10.1097/cad.0000000000001338
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytoclastic vasculitis presenting clinically as bullous pyoderma gangrenosum following leucovorin, fluorouracil and oxaliplatin chemotherapy: a rare case report and literature review

Abstract: There are no published cases about bullous pyoderma gangrenosum induced by leucovorin, fluorouracil and oxaliplatin (FOLFOX) chemotherapy. With the increasing incidence of gastric and colorectal cancers and the increased usage of targeted therapies, some cutaneous adverse effects may become common. An 84-year-old male presented to our clinic with multiple ulcerative plaques covered with hemorrhagic crusts on both extremities after several FOLFOX chemotherapy sessions for gastric cancer and liver metastasis. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Currently, there are no reports of AAV induced by oxaliplatin or capecitabine. However, multiple reports have indicated that oxaliplatin can cause cutaneous vasculitis [ 1 , 2 ] and leukocytoclastic vasculitis [ 3 , 4 ]. Capecitabine-induced leukocytoclastic vasculitis has also been reported [ 5 , 6 ].…”
mentioning
confidence: 99%
“…Currently, there are no reports of AAV induced by oxaliplatin or capecitabine. However, multiple reports have indicated that oxaliplatin can cause cutaneous vasculitis [ 1 , 2 ] and leukocytoclastic vasculitis [ 3 , 4 ]. Capecitabine-induced leukocytoclastic vasculitis has also been reported [ 5 , 6 ].…”
mentioning
confidence: 99%